2021
DOI: 10.3389/fphys.2021.695779
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cardiovascular Dysfunction With PDE5-Inhibitors – Temperature Dependent Effects on Transport and Metabolism of cAMP and cGMP

Abstract: IntroductionCardiovascular dysfunction is a potentially lethal complication of hypothermia. Due to a knowledge gap, pharmacological interventions are not recommended at core temperatures below 30°C. Yet, further cooling is induced in surgical procedures and survival of accidental hypothermia is reported after rewarming from below 15°C, advocating a need for evidence-based treatment guidelines. In vivo studies have proposed vasodilation and afterload reduction through arteriole smooth muscle cGMP-elevation as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 49 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Pentoxifylline (Sigma-Aldrich, St. Louis, MO, USA) was used in all experiments. Detailed methods for assessing intracellular access, enzyme inhibition and cellular efflux were first described in earlier publications [14,15].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pentoxifylline (Sigma-Aldrich, St. Louis, MO, USA) was used in all experiments. Detailed methods for assessing intracellular access, enzyme inhibition and cellular efflux were first described in earlier publications [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…The articles had to report adult human data and cardiovascular condition to be considered. Pentoxifylline was incubated at a final concentration of 100 µM as this corresponded to the highest concentrations found in the review [14,15].…”
Section: Intracellular Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood was consistently collected from randomly assigned, pre-screened healthy blood donors. As described in our recent publication from the same project ( Selli et al, 2021 ), the regional ethical committee found that ethical review and approval was not required for this study, as the study was performed according to local legislation and institutional requirements included in our agreement with Department of Immunohematology and Transfusion Medicine, University Hospital of North Norway. The participants provided their written informed consent to contribute before sampling at Blodbanken, and we only received anonymized blood samples for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Each medication and control solution were tested in triplicates and at three independent experiments for each temperature. The study protocol has been described previously by our research group ( Selli et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%